High temperature oxidation kinetics of Ni-based alloys for aero-engine exhaust components - Sandberg,Nils (2025)
This thesis investigates the high-temperature oxidation kinetics of two nickel-based superalloys produced via additive manufacturing (AM), referred to as alloy A and alloy B, in comparison to the conventionally cast superalloy MAR-M 247. The study focuses on oxide scale growth, morphology, and depletion zone development under semi-isothermal conditions at temperatures below 900°C and 1000°C over exposure periods ranging from 20 to 1000 hours. Oxidation behavior was analyzed using light optical microscopy (LOM) to characterize oxide and depletion zones, and kinetic parameters were determined by fitting experimental data to generalized oxidation rate laws. Results indicate that surface preparation significantly influences oxide scale formation and that AM alloys do not display distinct oxidation kinetics and morphologies compared to MAR-M 247 in general. Among the alloys investigated though, there were variations in spallation behavior and scale stability. These findings contribute to the understanding of oxidation mechanisms in AM alloys and provide insight into their suitability for high-temperature aerospace applications, where material durability and oxidation resistance are critical.
Keywords: oxidation; kinetics; nickel-based alloys; additive manufacturing; aerospace applications; materials chemistry